THE INTERACTION BETWEEN RENEWABLE ENERGY SOURCES AND THE OIL AND GAS INDUSTRY - Pattakhov Dilshod (Modern American Journals, 2025)
This article explores the interaction between renewable energy sources and the oil and gas industry within the framework of the global energy transition. The study highlights the theoretical foundations of renewable energy development, the current role of the oil and gas sector in the world economy, and the dynamic process of energy substitution. It analyzes global trends, including investment flows, technological progress, and case studies from leading regions such as the United States, the European Union, China, and the Middle East. The research demonstrates that renewable energy is not replacing fossil fuels abruptly but gradually integrating into the global energy system, thereby reshaping the strategic priorities of oil and gas companies. The study emphasizes that the interaction between renewable and fossil energy sources is characterized by both competition and cooperation, and their balanced development is crucial for ensuring energy security and sustainability.
Keywords: Renewable energy, oil and gas industry, energy transition, sustainability, investment flows, global energy system, solar power, wind energy, hydrocarbons, green technologies.